The Malay Structure and Aesthetics in Classical Malay Romantic Poetry - Karim, Maizar; Warni, Warni; Afria, Rengki (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
This research explores Malay formal, narrative, and aesthetic structures in classical Malay romantic poetry, using qualitative methods and an eclectic study model (structuralism, hermeneutics, and aesthetics). The data of this research are Syair Abdul Muluk and Syair Dandan Setia. The formal structure of these poems is built by the elements of rhyme, rhythm, diction, array, and stanza, which are harmoniously interwoven and strictly follow the conventions of traditional Malay Syair. The narrative structure of the poem is built by the elements of plot, setting, character and characterization, theme, and mandate. These elements are functional and closely interwoven so that the story becomes intact and organic in building the meaning of the work. Malay aesthetics in this poem is categorized into several aspects, namely ontological, immanent, and psychological aspects. In the ontological aspect, it shows a series of words that are sourced from God's wealth which is simple, complete, and natural. Malay aesthetics in this conception corresponds to Islamic aesthetics that beauty comes from divine creative potential. In the immanent aspect, it describes something astonishing (amazing), describing something various or diverse that is full of harmony. On the psychological aspect, it relates to the extraordinary, the sightseeing of the soul, causing a sense of fascination or lust in the soul, giving birth to a sense of awe, even resulting in self-forgetfulness, and fainting.